Social Networks, Technology Adoption and Technical Efficiency in Smallholder Agriculture: The Case of Cereal Growers in Central Tanzania - Muange, Elijah (My University, 2014)
Global demand for food and agricultural products is on the rise. There is hence the need to increase production to meet this growing demand and smallholders will play a significant role. One strategy for smallholders to sustainably increase agricultural production is the use of modern productivity-enhancing technologies such as improved crop varieties. Investments in global agricultural research have resulted in the development and release of thousands of new varieties since the first Green Revolution. However, especially in Sub-Saharan Africa, traditional varieties still dominate smallholder farming, limiting the envisaged output and productivity gains. Lack of agricultural information is often cited as a major constraint to adoption of improved varieties, and the role of social networks in diffusion of information relevant for adoption of these varieties is increasingly being studied. This research contributes to the growing literature by looking at a number of elements that to the best of our knowledge have not been studied before. First, most studies on social network effects in agricultural technology diffusion tend to focus on networks within villages (intra-village networks). In this study, we look at effects of social networks across villages (intra-village networks) as well. Furthermore we explore other types of networks, in particular to community leaders (village administrators), who are part of formal information dissemination channels. Second, while the role of social networks in cereal farming has been investigated in the context of well-developed private seed markets, we do not find any studies assessing the role of social networks in situations where seed markets are underdeveloped. This study investigates effects of social networks in two contexts: one with developed seed markets and the other with frequently failing seed markets. Third, studies linking social networks to new agricultural technologies tend to focus on technology diffusion. However, information conveyed through social networks might also affect other farming practices and hence we investigate also the effects of social networks on technical efficiency. The main objective of this dissertation is to assess social networks and their explicit role in technology adoption and technical efficiency in smallholder agriculture. Using data collected from 345 cereal growers in Central Tanzania between September and November 2012, we focus on improved varieties of sorghum and maize, the staple cereals in the study area. Improved varieties of sorghum in Tanzania are characterized by underdeveloped private seed markets, while those of maize have mostly functioning private seed markets. This enabled us to make interesting comparisons that have not been made before. Our specific objectives are (1) to assess the factors that determine the existence of network links for the exchange of agricultural information between farmers, (2) to examine the role of social networks in exposing farmers to improved sorghum and maize varieties and hybrids (as a precondition for adoption of the technologies), (3) to assess the effects of social networks on adoption of improved varieties, and (4) to investigate the role of social networks for technical efficiency. In addition to descriptive analyses, a number of econometric tools were developed and used to achieve the objectives. These include dyadic regressions to identify determinants of network links, Poisson regressions to assess exposure to improved varieties, and the average treatment effect (ATE) framework to analyze adoption while controlling for nonexposure bias. To analyze technical efficiency, a stochastic frontier framework was applied. Propensity score matching techniques were used to control for endogeneity in the stochastic frontier analysis. We find that even at the lowest administrative unit, the sub-village, not all farmers know each other. Interestingly, even in the cases where farmers know one another, only about one third of randomly drawn pairs of such farmers exchange agricultural information. The exchange of relevant information is more likely between farmers who have similar levels of education, different farm sizes, are members of the same community association, live in the same village, have known each other for a longer time, have kinship ties, and if one of them is a community leader or has a direct link to a public extension officer. These patterns are almost the same for sorghum and maize, meaning that if farmers exchange farming information, they are unlikely to limit this exchange to certain crops. Farmer-to-farmer networks are important sources of first information on improved sorghum and maize varieties, with neighbors and friends playing a bigger role than relatives. Moreover, controlling for other farmer characteristics, we find that increasing the size of a farmer’s network increases the farmer’s intensity of exposure (number of varieties known) to improved varieties of sorghum, but not to those of maize. Further disaggregation of maize varieties shows that while larger social networks increase farmers’ exposure to open pollinated varieties (OPVs), the result remains insignificant for hybrids. Seed markets for hybrids are more developed than those of OPVs. Hence, the flow of information through informal networks is more important for seed technologies for which formal markets fail. Strikingly, inter-village networks play a larger role in creating awareness about new varieties than intra-village networks. Other results show that by networking with public extension officers and village administrators, farmers increase their exposure to improved varieties considerably. We conclude that informal information channels complement, but do not substitute awareness creation through formal channels.Consistent with expectations, we find evidence that for both crops, lack of exposure is indeed a constraint to the adoption of improved varieties, signaling a need to create more awareness. Interestingly, even after accounting for the role of social networks in exposure, and controlling for the intensity of exposure, we find that social networks for sorghum have a positive effect on variety adoption. We do not find significant social network effects on adoption of improved maize varieties, implying that the influence of social networks on adoption is greater for improved varieties whose markets often fail. Contrary to the influence of social networks on exposure, it is the intra-village and not inter-village networks that produce this effect in the case of sorghum. It means that while inter-village networks are more important for learning about new varieties as shown above, intra-village networks play a more important role in adoption. Network links with village administrators or extension officers do not influence adoption significantly, meaning that in the adoption process, formal channels are more relevant for the first step, which is, raising awareness. Finally, while the total and intra-village network sizes do not significantly influence technical efficiency, the inter-village sorghum network size has a positive effect on technical efficiency of improved but not of traditional varieties of sorghum. When comparing between improved varieties of the two crops, we conclude that social network effects are more relevant for varieties that do not have functioning private seed markets, consistent with the findings for exposure and adoption. Networking with village administrators did not have any significant effect on technical efficiency, but having links to the public extension officers and attending technology and information dissemination events organized through the officers had a positive effect on technical efficiency for improved varieties of maize. This shows that efficiency-enhancing production information for the largely commercialized seed technologies may be much more technical, hence requiring more specialized dissemination. The findings raise a number of implications for policy and future research. First, social networks matter for the spread and efficient utilization of new agricultural technologies. Hence, technology dissemination programs should try to make use of such networks. Second, inter-village networks matter for farmers’ exposure to and technical efficiency of improved varieties; hence facilitation of information exchange across village boundaries may improve awareness creation and the spread and productivity of new technologies. Third, the power of farmer networks with community leaders and village administrators can be exploited for increased awareness of improved technologies. Fourth, extension officers facilitate discussions about crop farming, and help in increasing awareness and technical efficiency of improved technologies. Therefore, new extension models could be developed that explicitly build on the synergies between formal and informal information channels.